JOURNAL OF GOVERNMENT & POLITICS : Social Movement of Mandar People as a Struggle in Processof Forming West Sulawesi Province - Gustiana A. Kambo (FISIPOL UMY, 2014)
This paper examines the dynamics of ethnicity in South Sulawesi.